Mitigating Long-Term COVID-19 Consequences on Brain Health - D'Arcy, Ryan C. N.; Sandhu, Jagdeep K.; Marshall, Shawn; Besemann, Markus (Frontiers in Neurology, 2021)
COVID-19 is increasingly being linked to brain health impacts. The emerging situation is consistent with evidence of immunological injury to the brain, which has been described as a resulting “brain fog.” The situation need not be medicalized but rather clinically managed in terms of improving resilience for an over-stressed nervous system. Pre-existing comparisons include managing post-concussion syndromes and/or brain fog. The objective evaluation of changes in cognitive functioning will be an important clinical starting point, which is being accelerated through pandemic digital health innovations. Pre-morbid brain health can significantly optimize risk factors and existing clinical frameworks provide useful guidance in managing over-stressed COVID-19 nervous systems.